Analisis Penggunaan Aplikasi Whatsapp pada PT. Bank Perkreditan Rakyat Sulawesi Mandiri - karta negara salam; Rhima Narulita Ikhwanah Amin (LP2M IBK Nitro, 2021)
The purpose of this study was to analyze the use of the WhatsApp application at PT. Sulawesi Mandiri People's Credit Bank. The analytical method used is descriptive qualitative in the form of an interview at PT. Sulawesi Mandiri People's Credit Bank. The results showed that the use of the WhatsApp application was used by employees at PT. Sulawesi Mandiri People's Credit Bank Mandiri because it can support work in team and individual work.